Assessment of brake wear emissions from a brake rig - Suresh, Nandu (My University, 2024)
As the number of vehicles on the road continues to rise, and solutions for exhaust emissions have been developed, non-exhaust emissions are becoming increasingly prominent, particularly brake wear emissions. Non-exhaust emissions could be extremely harmful to humans and can cause premature deaths. Hence it is necessary to identify the problematic particles among the brake particles to mitigate the harmful effect of brake wear emissions on health. This project aims to find the properties and composition of brake particles generated from a brake system comprising a brake disc and a pair of brake pads of a light-duty vehicle. With multiple standardised driving cycles available, rig-based testing can be done with proper infrastructure, and brake particles can be sampled and analysed properly. The new upcoming Euro 7 legislation limits the PM10 emissions from the brakes of light-duty vehicles to 3 mg/km. Brake particles were generated using a custom drive cycle suitable for the operation of the brake rig, followed by the sampling and assessment of the particles using Dekati ELPI+ and further analysis was done using SEM-EDX to get microscopic pictures of brake dust as well as its chemical composition. For the test cycle and operating conditions, most of the particles formed were in the region of PM10. Particle size distribution (PSD) curves are plotted for a better understanding of different conditions like the re-suspension of brake particles. The effects of temperature, brake pressure and speed on the formation of brake particles are analysed in the form of PSD curves. Metals like Fe and Ca were found to be the dominant materials among the larger particles and elements like C, O, Si etc made up most of the smaller particles. Principal component analysis, together with SEM-EDX results validates that.
Keywords: Euro 7; Particulate Matter(PM); PM10; PM2.5; SEM; EDX; Brake wear; PSD; PCA; Respiratory health